MANAGE OF JOB STRESS AND MEASURE EMPLOYEE PERFORMANCE IN HEALTH SERVICES - Abdul Haeba Ramli (Business and Entrepreneurial Review, 2018)
This research on health service employees who are in Jakarta wants to observe the work stress experienced and how the risks will arise from organizational commitment and employee performance. The design of this research is to use a survey method with cross-section data collection using a questionnaire. A total of 82 employees of the Private Hospital consisting of Doctors, Nurses and Staff as respondents in this study, were determined by utilizing the simple random sampling method. The data analysis method used is Structural Equation Modeling (SEM) as a design in analyzing data analysis on testing research hypotheses. The results of the study present the results that work stress has a negative and significant impact on organizational commitment, then work stress that has a negative and significant impact on employee performance, then high organizational commitment can actually cause a positive and significant impact on employee performance.